2020
DOI: 10.3390/s20030663
|View full text |Cite
|
Sign up to set email alerts
|

The Rehapiano—Detecting, Measuring, and Analyzing Action Tremor Using Strain Gauges

Abstract: We have developed a device, the Rehapiano, for the fast and quantitative assessment of action tremor. It uses strain gauges to measure force exerted by individual fingers. This article verifies the device’s capability to measure and monitor the development of upper limb tremor. The Rehapiano uses a precision, 24-bit, analog-to-digital converter and an Arduino microcomputer to transfer raw data via a USB interface to a computer for processing, database storage, and evaluation. First, our experiments validated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…While wearable sensors have the advantage of monitoring patients in several situations, devices that do not require attachment to the patient are also useful while measuring behavioral tremors under specific conditions. This led to the development of Rehapiano, an ergonomically designed tremor evaluation device with strain gauges placed on a two-handed handle [ 79 ]. The performance evaluation also confirmed that the sensitivity was sufficient to quantify the tremor.…”
Section: Resultsmentioning
confidence: 99%
“…While wearable sensors have the advantage of monitoring patients in several situations, devices that do not require attachment to the patient are also useful while measuring behavioral tremors under specific conditions. This led to the development of Rehapiano, an ergonomically designed tremor evaluation device with strain gauges placed on a two-handed handle [ 79 ]. The performance evaluation also confirmed that the sensitivity was sufficient to quantify the tremor.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies were based on classic load cell force sensors (Kruchinin et al, 2013;Safyannikov, Bureneva, Zhirnova, 2018;Blakemore et al, 2018;Christou et al, 2004;Ferenčík, Jaščur, Bundzel, & Cavallo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have utilized tools such as pens [ 25 30 ] with embedded IMUs and load cells to quantify tremor amplitude while users hold it, attach it to their hands, or write with it. An advantage of embedded sensor tools is their ability to identify different features in virtual tasks [ 31 33 ]. For example, the Virtual Peg Insertion Test (VPIT), based on the 9HPT [ 34 ] test, employs a manipulandum with force sensors in a virtual game environment and serves as a digital health metric for predicting the response to neurorehabilitation interventions in neurological disorders.…”
Section: Technologies For Tremor Assessmentmentioning
confidence: 99%